Rare Case of Solitary Nasal Fibrous Tumor Eroding Skull-Base - Bhati, Aditendraditya Singh; Rana, Nishant; Raheja, Girish; Tyagi, Sudheer K. (Asian Journal of Neurosurgery, 2022)
Solitary fibrous tumor (SFT) is a spindle cell lesion, classified under mesothelial tumors. Involvement of the nasal cavity, paranasal sinuses, and nasopharynx is rare. We present an extremely rare case of SFT of nasal origin eroding the anterior skull base. Complete local excision is the treatment of choice in the head and neck SFT, and we successfully excised the tumor by endoscopic approach only. The patient followed an uneventful course without any evidence of recurrence on 8-months follow-up.
Keywords: solitary fibrous tumor; nasal; anterior skull base; endoscopic excision; CD34